Entrepreneurship: A scope for Employment in India - K., Manjunatha (IJRDO - Journal of Business Management, 2017)
Entrepreneurship is not new concept to India, being older to Indians has made its own mark in supporting the economic growth of nation. As India is developing country, is facing number of socio-economic problems like poverty, unemployment, illiteracy, etc. The economic and social progress of a nation is measured by a strong sector of entrepreneurship as it directly pillars the development of nation. Therefore micro, small and medium enterprises are significant as they create jobs either as a self employee or create vast opportunities for jobs by making them a successful businessman. Entrepreneurship has become a bridge between an individual and national economic growth through the process of training the individuals with all kinds of potential skills. At this juncture certain entrepreneurial training institutes behave as catalyst agents. Out of gender bias and marginalization, women have received an identity as an ‘woman entrepreneur’ in the current globalised era. According to the 12th 5 year plan 30% of government schemes are being utilized by women and female children in the form of fund for business/schooling.